Haemophilia, Past and Present (Res Medica, 2014)
INTRODUCTIONThe term haemophilia, meaning “lover of blood", was coined comparatively recently in the long history of bleeding disorders, having been first used in the early 19th century. Then it defined a bleeding disorder which was transmitted by certain unaffected females to some of their sons. Now, as a result of the enormous increase in scientific knowledge developed in the interim, haemophilia can be defined more precisely as a coagulation disorder transmitted in a sex-linked recessive manner and primarily expressed in males, in which the level of factor V I II clotting (or biological) activity in the blood is reduced below normal because some of the precursor molecules, (named immunological factor V III), are functionally abnormal and cannot be converted to clotting factor V III. The clinical grade of severity of the disorder breeds true and correlates well with the amount of circulating clotting factor V III, severely affected haemophiliacs having less than 1%, moderately affected between 1 and 5% and mildly affected between 5 and 50%. The normal range is 50 - 200%.